AUDITOR SPESIALISASI INDUSTRI DAN EFEKNYA PADA MANAJEMEN LABA - Nany Chandra Marsetio; Retno Yuliati (Faculty of Economics and Business, Universitas Warmadewa, 2022)
This paper presents the evidence regarding the relationship between auditor industry specialization and accrual earning management. Auditor industry specialization was measured by four continuous and four dummy variables. It was proxied by market share total asset, market share number of clients, the interaction between market share total asset and portfolio share, and interaction between market share number of clients and portfolio share. Earning management was proxied by accrual discretionary modified jones. Samples of this study were 1,668 nonfinancial firm-years listed in IDX during the 2012-2019 period. We restricted our study to clients of Big 10 auditors. Hypothesis testing used regression panel data. Fixed effect regression finds that auditor industry specialization proxied by market share total asset positively impacts earning management modified jones. The research contributes to the literature by highlighting the positive relationship between auditor industry specialists and earning management. This result was contradictive with previous findings make this become fruitful further research.